Hybrid de novo whole-genome assembly and annotation of SARS-CoV-2 Virus from nosocomial infection in Pahang, Malaysia - Zainulabid, Ummu Afeera; Kamarudin, Norhidayah; Mohd Rus, Razman; Soffian, Sharmeen Nellisa; Mat Yassim, Aini Syahida; How, Soon Hin; Ahmad, Hajar Fauzan (Elsevier, 2022)
Purpose SARS-CoV-2 virus is highly contagious and spreads easily that it is difficult to detect in elucidating the pattern of infection for contact tracing purposes. The advent of high-throughput sequencing techniques has improved diagnosis in detection the viral lineages especially involving sporadic infection. The combination of short- and long-reads greatly improved the assembly of the SARS-CoV-2 genome and marked as a new approach to correct erroneous frame-shifts from single sequencing effort.